Evolution and Conservation of Bordetella Intracellular Survival in Eukaryotic Host Cells - Rivera, Israel; Linz, Bodo; Harvill, Eric T. (Frontiers in Microbiology, 2020)
The classical bordetellae possess several partially characterized virulence mechanisms that are studied in the context of a complete extracellular life cycle in their mammalian hosts. Yet, classical bordetellae have repeatedly been reported within dendritic cells and alveolar macrophages in clinical samples, and in vitro experiments convincingly demonstrate that the bacteria can survive intracellularly within mammalian phagocytic cells, an ability that appears to have descended from ancestral progenitor species that lived in the environment and acquired the mechanisms to resist unicellular phagocytic predators. Many pathogens, including Mycobacterium tuberculosis, Salmonella enterica, Francisella tularensis, and Legionella pneumophila are known to parasitize and multiply inside eukaryotic host cells. This strategy provides protection, nutrients, and the ability to disseminate systemically. While some work has been dedicated at characterizing intracellular survival of Bordetella pertussis, there is limited understanding of how this strategy has evolved within the genus Bordetella and the contributions of this ability to bacterial pathogenicity, evasion of host immunity as well as within and between-host dissemination. Here, we explore the mechanisms that control the metabolic changes accompanying intracellular survival and how these have been acquired and conserved throughout the evolutionary history of the Bordetella genus and discuss the possible implications of this strategy in the persistence and reemergence of B. pertussis in recent years.